History and Heresy - Kelly, Joseph F. (Joseph Francis), 1945- (Book collections on Project MUSE., 2012)
Heresies, like doctrinal formulations, are products of history. They must be understood historically as well as theologically. When doctrinal issues become intertwined with historical ones, advocates of a new understanding have often run afoul of religious authorities. In History and Heresy, Joseph F. Kelly first describes how the concept of orthodoxy developed. Then he examines five heresies -- Montanism, Monophysitism, Catharism, Catholic Modernism, and Protestant Modernism and Fundamentalism -- in their historical contexts and the significant role that historical forces played in their designation as heretical. Finally, he suggests ways that religious authorities today can evaluate historical factors when making judgments about whether a particular idea is truly a heresy. Real heresy, Kelly contends, represents a clear and present danger to Christian teaching and demands a response from the church. But determining heresy is an exercise that must be undertaken with great wisdom and study.